1975
DOI: 10.1021/i260053a011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Gas from Bovine Wastes

Abstract: acetic acid solution catalyzed by aluminum chloride, the successive reaction can proceed selectively, differing from the reaction without a catalyst. Under conditions of a bench-scale reactor, stirring being used, the relative flow rate of chlorine being 0.25 to 0.60, the concentration of BPA feed 10%, that of the catalyst more than 1%, and the reaction temperature 30 to 33°C, the selectivity of the catalyst for the formation of DCBPA and TCBPA was very high. The reaction apparently proceeded through three sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
6
0
Order By: Relevance
“…Thermal gasification has been perhaps the most studied thermochemical process (in terms of the amount of publications) intending to transform dairy manure into value-added byproducts (e.g., fuel gases and liquids), as reported in a number of works [153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177,178,179]. However, as stated by the Midwest Energy Research Center 23 [180], no operational farm-scale gasification systems have been identified in the United States but research has been conducted only at laboratory or pilot scale.…”
Section: Thermal Gasificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Thermal gasification has been perhaps the most studied thermochemical process (in terms of the amount of publications) intending to transform dairy manure into value-added byproducts (e.g., fuel gases and liquids), as reported in a number of works [153,154,155,156,157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177,178,179]. However, as stated by the Midwest Energy Research Center 23 [180], no operational farm-scale gasification systems have been identified in the United States but research has been conducted only at laboratory or pilot scale.…”
Section: Thermal Gasificationmentioning
confidence: 99%
“…As a result, a number of works on gasification of dairy manure were conducted during the 1970s [153,154,155,161,162,163,164]. Engler et al [155] evaluated a concept for gasification of feedlot manure considering the advantages of simultaneously producing gases (which were envisioned that could be used for power generation, raw material for ammonia synthesis, or raw material for methanol production) and ash by-product potentially usable as a fertilizer.…”
Section: Thermal Gasificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments were conducted in a 5 cm diameter reactor and used recycled product gas and air as the gas medium. The data were obtained for a temperature range of 894 to 950 K. Bench scale operating data were obtained by Halligan et al (1975) in a 5 cm diameter reactor, which was operated in a partial combustion mode with steam and air. The reactor was externally heated with electrical heaters, and the data were obtained between 966 and 1069 K. Mikesell et al (1978) reported limited data on the flash pyrolysis of steer manure in a multiple hearth reactor.…”
Section: Introductionmentioning
confidence: 99%